European fiscal reform preferences of parliamentarians in France, Germany and Italy - Blesse, Sebastian; Bordignon, Massimo; Boyer, Pierre C.; Carapella, Piergiorgio; Heinemann, Friedrich; Janeba, Eckhard; Raj, Anasuya (European Union politics, 2022)
Using data from a unique survey of members of parliaments in France, Germany and Italy in 2018, we estimate the effects of three dimensions on EU and Euro Area fiscal reform preferences: nationality, political ideology and populism. We predict and confirm that a German populist party on the right is most opposed to a more developed European fiscal union, while a non-populist politician on the political left in France or Italy is most integrationist. Furthermore, the relative position of French and Italian policymakers is issue dependent and the left dimension outweighs the German dimension in two out of seven reform issues. Finally, populism intensifies the polarizing impact of national interests.